Revision of Sarcocornia (Chenopodiaceae) in South Africa, Namibia and Mozambique - Steffen, S.; Mucina, Ladislav; Kadereit, G. (The American Society of Plant Taxonomists, 2010)
Sarcocornia comprises ca. 20–24 perennial, halophytic herb and shrub species. The genus is distinct from other genera in the Salicornioideae in having flowers that are more or less equal in size, arranged in a row, and with seeds that have a membranous hairy testa and lack perisperm. Sarcocornia is distributed worldwide, mainly in regions characterized by warm-temperate and, to a lesser extent, subtropical climates. The representatives of this genus are found in habitats such as estuarine salt marshes, tidal mud flats, coastal cliffs, inland salt pans, and salt-laden alluvia of intermittent semi-desert and desert streams. Some South African taxa also occur in inland (semi-desert) quartz patches while some South American species occur on saline soils of dry, continental high plateaus in the Andes. The genus reaches its highest species diversity in the Greater Cape Floristic Region of South Africa, where twelve species and one subspecies are known. This revision of southern African (South Africa, Namibia, and Mozambique) Sarcocornia comprises an identification key, the descriptions of the genus, species, and subspecies. One new combination, S. dunensis, is proposed. The former varieties recognized within S. natalensis are here treated as subspecies, S. natalensis subsp. natalensis and subsp. affinis. Morphological characters of high taxonomic value in the genus are habit (growth-form), segment morphology, and testa micromorphology. Our revision also features information on the distribution and ecology of the studied taxa.